Population Growth and Education in the Indian Scenario Since Independence: Exploring the Impact of Population Growth on Education in Post-Independence India (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The paper explores the intricate relationship between population growth and education in postindependenceIndia. With India gaining independence in 1947, the dynamic interplay between populationdynamics and the educational landscape has significantly impacted the nation's socio-economictrajectory. The paper critically examines this relationship by analyzing statistical data, policy documents,and academic literature to shed light on the evolution of population growth and educational initiatives. Thepost-independence era witnessed ambitious educational reforms driven by the recognition of education'srole in socio-economic development. The establishment of the University Grants Commission (UGC) in1953 aimed to enhance higher education quality and accessibility. Subsequent policies, including theNational Policy on Education (1968) and the Right to Education Act (2009), further strengthened India'scommitment to education. Education was identified as both a solution and a challenge in the context ofpopulation growth. While education, especially female education, has been acknowledged asinstrumental in reducing fertility rates, the growing population has strained the education system,necessitating innovative approaches to meet demand.The post-independence era in India has witnessed a complex interplay between population growth andeducation. The nation's journey reflects achievements and ongoing challenges in managing populationgrowth while nurturing a robust education system. This research paper contributes to the discourse onsustainable development and informed policymaking by providing a comprehensive understanding ofthe linkages between population growth and education in India.